The Evolution of the Foreign Policy of Italy - Kotúčová, Michaela (2015)
This paper work analyses the foreign policy of Italy from its foundation in 1861 until nowadays. Its main aim is to provide a comprehensive overview of the Italian actions and its position within the international system as well as to examine core objectives, means and factors of the Italian foreign policy making. The country went through different stages during its 154-year existence and experienced various types of state organisation and ideologies which were all reflect in its foreign policy making. The analysis verifies that the approach to the foreign policy making, targets and means to achieve them in Italy differed in each phase. These phases were the Kingdom of Italy, the First Republic and the Second Republic. Hence, the foreign policy of Italy is examined in the framework of these stages and each chapter thus corresponds to one of them. A theoretical chapter is also incorporated into this paper work in order to facilitate the understanding of the forthcoming analysis further in the text.